Zaboravljena lica ruske cenzure - Peruško, Ivana (Slavistična revija, 2012)
The article deals with the unbreakable connection between the art of writing and the diminished freedom of expression in Russian culture. Wishing to point out the ambivalent role of literature in the Russian culture, the author analyzes two pivotal moments in the history of Russian censorship that to a large extent predetermined the period of the total Stalinist censorship. Although this period is discussed in all cultural and historical studies dealing with the relationship between the writer and the government, the author points out the hitherto neglected roles of Peter the Great and Nicholas I, while also demystifying Lenin's free cultural policy.
Keywords: 20.st.; cenzura; Lenin, Vladimir Il'ič, 1870-1924; ruska književnost; ruska kultura; Russian literature